Design and Implementation of Quantity Calculation Method Based on BIM Data - Chen, Binjin; Jiang, Shaohua; Qi, Ligang; Su, Yawu; Mao, Yufeng; Wang, Meng; Cha, Hee Sung (Sustainability (Switzerland), 2022)
Manual quantity takeoff using two-dimensional (2D) drawings and personal knowledge is error-prone and time-consuming. Theoretically, quantity can be automatically calculated from building information model more quickly and reliably by extracting geometric data and semantic attributes of building elements. Specific construction classification systems embedded in mainstream modeling software for building information modeling (BIM) make it difficult for countries adopting different systems to calculate quantity directly. This paper proposes a BIM-based quantity takeoff code mapping (BQTCM) method to solve the above issue, and develops a quantity takeoff code mapping plug-in (QTCMP) on a BIM modeling software based on the proposed BQTCM method to obtain an accurate bill of quantities directly and efficiently. Moreover, by conducting a statistical analysis and examining a case study, this paper verifies the accuracy and efficiency of quantity takeoff attained from the proposed BQTCM method and QTCMP.
Keywords: BIM technology; code mapping; construction classification system; quantity takeoff